PENGARUH CURRENT RATIO, NET PROFIT MARGIN DAN RETURN ON EQUITY TERHADAP HARGA SAHAM SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Udharie, Azzalia Ayunda; Kencana, Dwi Tirta; Rosmala Sari, Tri Darma (AKUNTANSI DEWANTARA, 2024)
This research aims to analyze the influence of Current Ratio (CR), Net Profit Margin (NPM), and Return On Equity (ROE) on share prices in Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange. The population in this research are companies listed on the Indonesia Stock Exchange for the period 2019 to 2022. The purposive sampling method was utilized to select 19 companies from the Food and Beverage Sub Sector for research purposes. This study collects data through documentation and analyzes it using panel data. The results of this study indicate that the CR variable partially does not have a significant effect on stock prices. The NPM variable partially has a positive and significant effect on stock prices. Meanwhile, the ROE variable has a positive relationship but has no effect on stock prices. The CR, NPM and ROE variables influence share prices simultaneously and can explain share prices in Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange by 23.6910%.